Quantitative biochemical characterization and biotechnological production of caspase modulator, XIAP: Therapeutic implications for apoptosis-associated diseases - Yun, Si-Eun; Nam, Min-Kyung; Rhim, Hyangshuk (Biochimica et biophysica acta, 2018)
Regulating apoptosis is a common and essential therapeutic strategy for cancer and neurodegenerative disorders. Based on basic studies of apoptotic mechanisms, various researches have attempted to overcome the pathogenesis of such diseases by activating or inhibiting apoptosis. Generally, the biochemical characteristics of the target molecules should be evaluated along with understanding of their mechanisms of action during drug development. Among apoptotic regulators, XIAP serves as a potent negative regulator to block apoptosis through the inhibition of caspase (CASP)-9 and -3/7. Although XIAP is an attractive target with such apoptotic-modulating property, biochemical and biophysical studies of XIAP are still challenging. In this study, the CASP-9 and -3/7 inhibitors XIAP, 242Δ and Δ230 were prepared using the pGEX expression system and biochemically characterized. These inhibitors were expressed in Escherichia coli at a concentration of ≥20 mg/L culture under a native condition with 0.01 mM IPTG induction. Notably, using a simple and rapid affinity purification technique, these CASP-9 and -3/7 inhibitors have been purified, yielding ≥5 mg/L culture at approximately 90% purity. We have determined that HtrA2 specifically binds to the BIR2 and BIR3 of XIAP at a 1:1 molecular ratio. Moreover, in vitro cell-free CASP-9 and -3/7 activation-apoptosis assays have demonstrated that these purified XIAP proteins dramatically inhibit CASP-9 and -3/7 action. Our system is suitable for biochemical studies, such as quantitation of the number of molecules acting on the apoptosis regulation, and provides a basis and insights that can be applied to the development of therapeutic agents for neurodegenerative disorders and cancer. •Development of a simple and rapid method for bacterial expression and purification of XIAP proteins, wild type, 242Δ, and Δ230•Structural verification of the purified XIAP proteins using GST pull-down with HtrA2•Functional verification of the purified XIAP proteins using cell-free caspase activation-apoptosis assays